1999
DOI: 10.1136/oem.56.8.548
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of lung cancer among sugar cane farmers in India.

Abstract: Objectives-To investigate the risk of lung cancer among sugar cane farmers and sugar mill workers. Methods-A case-control study was conducted based in six hospitals in the predominantly sugar cane farming districts of the province of Maharashtra in India. Newly diagnosed, histologically confirmed cases were identified from these hospitals between May 1996 and April 1998. Other cancers were chosen as controls and matched to cases by age, sex, district of residence, and timing of diagnosis. Results-Adjusting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
0
22
0
5
Order By: Relevance
“…2,5,[22][23][24] However, the risk of oral cavity cancer among sugarcane farmers was elevated among both light and heavy drinkers, suggesting that factors other than alcohol may contribute to occupational causation. Another possible confounder is selection bias; the mean age of the sugarcane worker controls was substantially older than other controls, so that our use of a dwelling unit-based sampling scheme may have under-ascertained younger sugarcane workers (Ͻ65 years of age) who were more likely to be migrant harvesting workers 15 with transient and/or substandard living conditions. 25 Further studies of cancer of the oral cavity in areas with a concentration of sugarcane workers, particularly in developing countries where harvesting is still performed by hand, are needed to replicate these findings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2,5,[22][23][24] However, the risk of oral cavity cancer among sugarcane farmers was elevated among both light and heavy drinkers, suggesting that factors other than alcohol may contribute to occupational causation. Another possible confounder is selection bias; the mean age of the sugarcane worker controls was substantially older than other controls, so that our use of a dwelling unit-based sampling scheme may have under-ascertained younger sugarcane workers (Ͻ65 years of age) who were more likely to be migrant harvesting workers 15 with transient and/or substandard living conditions. 25 Further studies of cancer of the oral cavity in areas with a concentration of sugarcane workers, particularly in developing countries where harvesting is still performed by hand, are needed to replicate these findings.…”
Section: Discussionmentioning
confidence: 97%
“…11,13 Although not known to cause oral cavity cancer, exposure to actinomycetes has been associated with chronic destructive granulomas or ulcers of the mouth. 14 Some studies of sugarcane workers have reported an increased risk of lung cancer and mesothelioma, [15][16][17][18] which may result from exposures to biogenic amorphous silica (BAS) fibers during harvesting 15,19 or to asbestos or crystalline silica in processing facilities. 15,17 The possible role of BAS fibers in cancer of the oral cavity is suggested also by the elevated rates of esophageal cancer in areas of China and Iran, 20,21 where BAS fibers are ingested in flour and millet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a striking example of the effect of differences in exposures is evident for lung cancer where most studies of farmers show a striking deficit, but sugar cane farmers and sugar mill workers show an excess. The excess among sugar cane workers is thought to be due to the high concentration of silica in sugarcane stems 17. Third, although exposures can be quite intense during the actual performance of some specific farm tasks, many tasks are performed only a few days each year and the cumulative exposure may not be great.…”
Section: Discussionmentioning
confidence: 99%
“…A exposição constante à poeira proveniente do solo e à fuligem da cana queimada pode determinar o aparecimento em trabalhadores rurais, principalmente em cortadores de cana, de doenças respiratórias como rinites, sinusites, bronquites e pneumonias alérgicas, agudas ou crônicas. Estes distúrbios podem levar ao aparecimento de processos inflamatórios pulmonares crônicos, como enfisema e atelectasia (17)(18) . A presença no solo de resíduos de agrotóxicos utilizados durante o plantio de produtos agrícolas e a exposição diária aos raios solares podem ocasionar o aparecimento de doenças cutâneas em trabalhadores rurais, como dermatites alérgicas e de contato, dermatites crônicas, queimaduras solares e envelhecimento precoce.…”
Section: Resultsunclassified